News from the Evidence Base : Findings from the 2016 Census of Canada - Pocock, Joanne (2017)
Keywords: Official Language Minority Community (OLMC)

QCGN Congratulates New MUHC Board and Pledges its Support - Quebec Community Groups Network (QCGN) (2017)

Language Training Program : Report on interviews with health and social services network respondents - Farley, Roger (Dialogue McGill, 2017)

A Website Created to Support English-speaking Patients from Eastern Regions in Quebec Traveling Away from Home for Medical Services - Community Health and Social Services Network (CHSSN) (2017)

Resources for Families with Special Needs - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Community Looks Forward to MUHC Resolution - Quebec Community Groups Network (QCGN) (2017)

Let's Shift the Focus to Underlying Issues at McGill University Health Centre - Quebec Community Groups Network (QCGN) (2017)

A Needs Assessment : Better Understanding the Current Situation of the Senior Population - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
This needs assessment was conducted as part of a community development process in the English-speaking community of Grosse-Ile, on the Magdalen Islands, Quebec. It is part of the follow- up to a community portrait that was developed through a participatory process in early 2015. The process involved the mobilization and engagement of a number of local stakeholders as well as community residents who expressed their views on a number of different themes. One of the issues that was highlighted by community members as a concern, even a priority, was that of the aging population within the ESC, having access to few services and limited support for caregivers.
Keywords: Official Language Minority Community (OLMC)

Une évaluation des besoins : mieux comprendre la situation actuelle des aînés - Burke, Helena; Craig, Lisa; Richardson, Mary (Council for Magdalen Islanders (CAMI), 2017)
Cette évaluation des besoins a été menée dans le cadre d’un processus de développement communautaire dans la communauté anglophone de Grosse-Île, aux Îles-de-la-Madeleine, Québec. Elle fait partie du suivi d’un portrait communautaire qui a été élaboré par le biais d’un processus participatif au début de 2015. Le processus a impliqué la mobilisation et l’engagement de plusieurs intervenants locaux ainsi que de résidents de la communauté qui ont exprimé leurs opinions sur un bon nombre de thèmes. L’un des enjeux qui a été souligné par les membres de la communauté comme une préoccupation, voire une priorité, était celui du vieillissement de la population au sein de la CAI, ayant peu de services et un soutien limité aux proches aidants.
Keywords: Official Language Minority Community (OLMC)

Bienvenue au Jeffery Hale votre résidence, votre milieu de vie : Guide d’accueil des résidents et de leurs proches - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Welcome to Saint Brigid’s Home Residential and Long Term Care Center : Welcome Guide for Residents and their Loved Ones - Jeffery Hale - Saint Brigid's (JHSB) (2017)

Health Passport : When Language Matters / Passport santé : Question de langue - Assistance and Referral Centre (ARC) (2017)

Répit et soutien aux aides-soignant / Respite and Support for Caregivers - Coasters Association (2017)

Building Together : Succesful Partnerships Between Community and the Health and Social Services System - Community Health and Social Services Network (CHSSN) (2017)
The Community Health and Social Services Network (CHSSN) coordinates a Quebec-wide health and social services “Adaptation Program” designed to enhance the vitality of English-speaking minority communities in Quebec by increasing access to existing health and social services for Englishspeaking Quebecers. The program is supported by an investment from Health Canada and has been undertaken in partnership with the ministère de la Santé et des Services sociaux (MSSS). An implementation agreement between CHSSN and the MSSS was concluded to incorporate the projects into Quebec’s initiatives to improve access to health and social services in English through partnerships between local English-speaking communities and health and social services system.
Keywords: Official Language Minority Community (OLMC)

Mobilizing / se Mobilisent - Community Health and Social Services Network (CHSSN) (2017)

Dialogue : Better Communication for Better Care - Dialogue McGill (2017)

Dialogue : Mieux communiquer pour mieux soigner - Dialogue McGill (2017)

Health and Social Service Resources for English-Speaking Communities in the East and North of Montreal : 2017 - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)

Health and Social Service Resources for the English-speaking Seniors in the East end of Montreal - Réseau de l’est de l’île pour les services en anglais (REISA) (2017)